Optoacustic Imaging - From Light to Sound? Optoakustische Bildgebung - Licht rein, Schall raus? - Hindelang, B.; Schoenmann, C.; Aguirre, J.; Ntziachristos, V.; Biedermann, T.; Darsow, U. (Aktuelle Dermatologie, 2020)
Optoacoustic imaging is a novel imaging modality based on the acquisition and processing of ultrasound signals generated by absorption of laser light within tissue. This method combines optical absorption contrast with high contrast deep in tissue and allows for morphological as well as molecular and functional imaging. Optoacoustic imaging can be performed label free or with contrast dyes and is non-ionizing. The technique is furthermore scalable which means that it can be used for macroscopic, mesoscopic, and microscopic imaging. In recent years several optoacoustic systems have been developed and used in a variety of fields in both preclinical and clinical research. Promising fields of application in dermatology include the examination of melanomas, sentinel lymph nodes and non-melanoma skin cancer as well as the characterization of inflammatory skin diseases. In this review we explain the technical basics of optoacoustic imaging and describe and discuss the current state of research in macroscopic, mesoscopic, and microscopic optoacoustic systems.
CRIS-Team Scopus Importer:2023-03-08